"IRIS SHELF" TECHNIQUE FOR MANAGEMENT OF POSTERIOR SEGMENT INTRAOCULAR FOREIGN BODIES. Issue 10 (October 2021) - Soliman, Wael; Tawfik, Mohamed A.; Abdelazeem, Khaled; Kedwany, Salma M.
Abstract : Purpose: To describe "iris shelf" technique for removal of posterior segment intraocular foreign bodies (IOFBs) through a corneal incision combined with phacovitrectomy and to report its outcomes. Methods: Medical records of patients with posterior segment metallic IOFBs who had combined phacovitrectomy were collected and analyzed. In all patients, the IOFB was placed on the iris surface after forming the anterior chamber with viscoelastic to be extracted through a corneal phacoemulsification incision. Results: Thirty-three eyes of 33 male patients with a mean age of 31.6 ± 8.3 years were included in the study. The mechanism of injury was hammering in 24 eyes (72.7%) and gunshot in 9 eyes (27.3%). The mean interval between injury and IOFB removal was 14.76 ± 6 days. The mean IOFB volume was 8.5 ± 5.5 mm 3, and its longest dimension was 3.45 mm (range, 1–8 mm). The mean preoperative corrected distance visual acuity changed from 20/1, 500 (1.79 logarithm of the minimum angle of resolution) to 20/94 (0.67 logarithm of the minimum angle of resolution), postoperatively ( P < 0.001). Postoperative complications included retinal detachment (two eyes), proliferative vitreoretinopathy (one eye), epiretinal membrane (one eye), and posterior synechiae (three eyes). Conclusion: The "iris shelf" technique with phacovitrectomy is a safe and reproducible approach for posterior segment IOFB extraction through a corneal incision with favorable visual and anatomical outcomes. Abstract : Supplemental Digital Content is Available in the Text.This study evaluates our preferred technique for the removal of posterior segment metallic intraocular foreign bodies. Iris is used as a shelf to support the intraocular foreign body after forming the anterior chamber with viscoelastic to accommodate the intraocular foreign body. Then, the intraocular foreign body is removed through a corneal incision. Corrected distance visual acuity improved in all patients.